Entre o pedagógico e o político: pensando contra-hegemonia e educação popular a partir do Práxis - coletivo de educação popular (Santa Maria - RS) - Dornelles, Lucas Augusto Schmidt (2021)
Praxis is a popular education collective, organized as a preparatory course for ENEM, linked to the Federal University of Santa Maria as an extension project, which claims popular education as a political-pedagogical perspective and is organized based on self-management. This research aims to understand the movement through which the collective (re)affirms the popular character of the project and projects itself as a social movement. In addition to a literature review, document analysis and semi-structured interviews were carried out with the educators, as well as with a project coordinator, in order to capture both the Praxis members' perceptions about popular education and the project's objectives, as for the strategies mobilized by the educators in this process, such as the insertion in social subprojects, the paradidactic activities, the interdisciplinary classes and the internal formation spaces. It was possible to observe that these strategies involve both the denaturalization, with educators and students, of proper elements of bourgeois sociability and traditional education, as well as the projection of Praxis beyond the walls of the university, inserting itself in the mobilizations and social struggles and taking a popular perspective to the projects in which it is inserted, notably with the prison system. It was possible to conclude that through this movement, Praxis constitutes an important agent of the democratization of culture and education in Santa Maria - RS, both through the preparatory classes for ENEM and the projects and activities in which it is inserted, as well as in a political agent, inserted in local social mobilizations and forming educators committed to an education that is capable of helping the subjects of the popular classes in their emancipation and humanization.